LABORATORY ANALYSIS OF POST-LYMPHATIC DRAINAGE URINE - Krupek, Tuane (2012)
The lymphatic system, an auxiliary pathway of the cardiovascular system, collects the liquid of interstitial spaces and macro-molecules which transport blood. The blood is then filtered by the kidneys, specifically by the glomerular structures, and urine is produced. The role of manual lymphatic drainage is the improvement of lymph flux conducted by the lymphatic system. It is usual that after this procedure some patients have a greater need to urinate, accompanied by the urine’s different aspect, without any information on changes in the literature. Twelve sessions of manual lymphatic drainage by Leduc technique were conducted in four female patients, age bracket between 20 and 35 years (± 24.2 years). Collection of urine was undertaken before and after the technique, with a 700 ml sterile flask. Further, samples were analyzed by the enzyme and colorimetric test for triglyceride dosage. Results were statistically analyzed: paired T test did not show any significant effect, whereas ANOVA registered an increase in urine’s mean volume after lymphatic drainage. A high mean quantity in glycerol volume was reported in collected samples before drainage, with differences among the participants. Tukey’s test registered that the participant with the lowest mean and who differed from the others was the subject who did not undergo all the proposed sessions. Effect of lymphatic drainage may be thus suggested.